Immunomodulatory Effects of Rhinovirus and Enterovirus Infections During the First Year of Life - Ruohtula, Terhi; Kondrashova, Anita; Lehtonen, Jussi; Oikarinen, Sami; Hämäläinen, Anu-Maaria; Niemelä, Onni; Peet, Aleksandr; Tillmann, Vallo; Nieminen, Janne K.; Ilonen, Jorma; Knip, Mikael; Vaarala, Outi; et al. (Frontiers in Immunology, 2021)
Early childhood infections have been implicated in the development of immune-mediated diseases, such as allergies, asthma, and type 1 diabetes. We set out to investigate the immunomodulatory effects of early viral infections experienced before the age of one year on the peripheral regulatory T-cell population (Treg) and circulating cytokines in a birth-cohort study of Estonian and Finnish infants. We show here a temporal association of virus infection with the expression of FOXP3 in regulatory T cells. Infants with rhinovirus infection during the preceding 30 days had a higher FOXP3 expression in Treg cells and decreased levels of several cytokines related to Th1 and Th2 responses in comparison to the children without infections. In contrast, FOXP3 expression was significantly decreased in highly activated (CD4+CD127-/loCD25+FOXP3high) regulatory T cells (TregFOXP3high) in the infants who had enterovirus infection during the preceding 30 or 60 days. After enterovirus infections, the cytokine profile showed an upregulation of Th1 and Th17 related cytokines and a decreased activation of CCL22, which is a chemokine derived from dendritic cells and associated with Th2 deviation. Our results reveal that immunoregulatory mechanisms are up-regulated after rhinovirus infections, while enterovirus infections are associated with activation of proinflammatory pathways and decreased immune regulation.